2005
DOI: 10.1002/pola.20587
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of random and block copolymers with pendant rhenium diimine complexes by controlled radical polymerization

Abstract: We report the polymerization of rhenium-containing methacrylates by atom transfer radical polymerization. The structure of the monomer was confirmed by X-ray crystallography, which showed the bulkiness of the metal-complex moiety. The rhenium complexes were polymerized in the presence of copper(I) bromide, 1,1,4,7,7-pentamethyldiethylenetriamine, and methyl 2-bromopropionate. They were copolymerized with methyl methacrylate in different monomer ratios. An ABA triblock copolymer was also synthesized with poly(m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Fluorinated segments is statistically incorporated into the side chains of linear polymers via copper-catalyzed polymerization of a pendant-fluorinated methacrylate and MMA (FR- 31 ) , or St (FR- 32 ) (Figure ). Additionally, copper-catalyzed system efficiently performs statistical copolymerization of bulky pendant-bearing monomers including a bulky hostasol moiety for FR- 33 , FR- 34 , a metal complex (FM- 75 ) for FB- 35 , and bulky/rigid biphenyl fluorine-bearing methacrylates (FM- 90 /FM- 99 ) for FB- 36 . The hostasol-tagged polymers (FR- 33 , FR- 34 ) obtained with FI- 54 or FI- 55 are applied to bioconjugation to efficiently work as fluorescently labeled polymers.…”
Section: Precision Polymer Synthesismentioning
confidence: 99%
“…Fluorinated segments is statistically incorporated into the side chains of linear polymers via copper-catalyzed polymerization of a pendant-fluorinated methacrylate and MMA (FR- 31 ) , or St (FR- 32 ) (Figure ). Additionally, copper-catalyzed system efficiently performs statistical copolymerization of bulky pendant-bearing monomers including a bulky hostasol moiety for FR- 33 , FR- 34 , a metal complex (FM- 75 ) for FB- 35 , and bulky/rigid biphenyl fluorine-bearing methacrylates (FM- 90 /FM- 99 ) for FB- 36 . The hostasol-tagged polymers (FR- 33 , FR- 34 ) obtained with FI- 54 or FI- 55 are applied to bioconjugation to efficiently work as fluorescently labeled polymers.…”
Section: Precision Polymer Synthesismentioning
confidence: 99%
“…The copolymerization of MMA with different Re(I) complex/ MMA ratios was demonstrated as well as the synthesis of an ABA triblock copolymer with PMMA, as macroinitiator. 175 Scheme 22 Schematic representation of poly(arylene ethynylene) (PPE) architectures containing Re(I) complexes. 186 The neutral Re(I) complex in the homopolymers and copolymers was further converted into an ionic form by replacing the chloride ligand by an imidazole ligand, thereby significantly enhancing the solubility of the resulting ionic polymers.…”
Section: Macromolecules Containing Pyridine-based Re(i) Complexesmentioning
confidence: 99%
“…On the other hand, the photochemistry of metal carbonyls has been the subject of extensive studies as well, and the topic was covered by several excellent reviews. The excited-state properties of rhenium­(I) tris -carbonyl complexes of general formula [Re­(CO) 3 (N^N)­L] n + , where N^N is an α , α ’-diimine ligand such as 2,2′-bipyridine or 1,10-phenanthroline and related derivatives and L = halogen (for n = 0) or a monodentate neutral ligand (for n = 1), were intriguing; for instance, a substituted phosphine or pyridine was first recognized in the mid-1970s. , Since then, photoactive Re­(I) complexes have attracted much interest. Previous studies have shown that the [Re­(CO) 3 (N^N)­L] n+ class of complexes are emissive from low-lying triplet excited states with a metal-to-ligand charge transfer ( 3 MLCT) character with sometimes admixed triplet ligand-centered ( 3 LC) manifold, namely 3 LC/ 3 MLCT, and are highly sensitive to environmental rigidity and changes. , Furthermore, depending on the nature of both the coordinated ancillary and diimine ligands, these complexes may display bright photoluminescence either in fluid solution at room temperature or at low temperature in glassy matrices. , Nevertheless, the photochemistry and photophysics of rhenium complexes is largely dominated by compounds bearing diimine type of ligands, , , whereas congeners bearing NHC ligands are much less explored to date. The first examples of such a family were reported in 2011 by Massi, and only a few other related compounds have been reported since, which mainly explored the coordination and optical properties of complexes featuring imidazolylidene and benzimidazolylidene scaffolds. …”
Section: Introductionmentioning
confidence: 99%